\(\frac { x }{ y } +\frac { y }{ z } +\frac { z }{ x } =\frac { y }{ x } +\frac { z }{ y } +\frac { x }{ z } =x+y+z=3\)

This a part of my set NMTC 2nd Level (Junior) held in 2014.

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewest\(\dfrac{x}{y}+\dfrac{y}{z}+\dfrac{z}{x}\ge 3\) by AM-GM, with equality case if and only if \(x=y=z\)

Since \(x+y+z=3\), then we know the only real solution is \((x,y,z)=\boxed{(1,1,1)}\)

Log in to reply

Good observation.

Note that the application of AM-GM assumes that the variables are positive.

Are there solutions over all reals?

What about over all complex numbers?

Log in to reply

\(minimum\quad value\quad of\quad \frac { x }{ y } \quad +\quad \frac { y }{ z } +\frac { z }{ x } =3\quad \\ from\quad this\quad how\quad can\quad we\quad conclude\quad that\quad x=y=z????\)

Log in to reply

Hint:Make common denominator for\( \frac{ x}{y} + \frac{y}{z} + \frac{z}{x} - \frac{ y}{x} - \frac{ z}{y} - \frac{ x}{z} \).Factorize the numerator.

Log in to reply

\( \frac{ x}{y} + \frac{y}{z} + \frac{z}{x} - \frac{ y}{x} - \frac{ z}{y} - \frac{ x}{z} = \frac{z-y}x+\frac{x-z}y+\frac{y-x}z=\frac{(z-y)zy+(x-z)xz+(y-x)yx}{xyz}=\frac{(y-z)(x-z)(y-x)}{xyz}=0\)

Therefore \(x,y,z\ne0\) and (\(y=z\) or \(x=z\) or \(y=x\)).

Log in to reply

Great work.

This is a short step away from finishing the solution.

Log in to reply

\(\frac xy+\frac yx=2\), \(\frac xy=1\), \(x=y\).

Therefore, \(x=y=z\).

From \(x+y+z=3\), we have \(x=y=z=1\) as the only real solution.

Log in to reply

x=1,y=1,z=1

Log in to reply

x=y=z=1 therefore the answer is 3 ,basic algebra question

Log in to reply

Write a comment or ask a question... (1,1,1)

Log in to reply

How do you know that there are no other solutions?

Log in to reply